Normative Framework of The Republic of Serbia Regulating the Issue of Conflicts of Interest: With Reference to the Practice of The Agency for the Prevention of Corruption - Stevanović, Aleksandar (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
This paper considers the phenomenon of conflict of interest, focusing on its main characteristics and manifestations in the normative framework of the Republic of Serbia. A normative concept depends on a variety of socio-political, cultural, economic, historical, traditional and other factors, so it could be concluded that conflict of interest is a kind of social construct. This means that it is necessary to take into account all of these causes in the notional definition of conflict of interest in relation to each individual society. The conflicts of different interests are an integral part of life in an organized community, and we can reasonably argue that the quality of such life, to a large extent, depends on the proper definition of the concept of conflict of interest and, accordingly, its adequate regulation. The general conclusion is that some insufficiently defined institutes and concepts, such as the notion of public office in the new Law on Prevention of Corruption, stimulate the state of affairs, which can be described as "a net that catches small and lets big fish through". The new Law on Prevention of Corruption, which has not resolved certain problematic areas, at least when it comes to the part of the Law dedicated to the prevention of conflicts of interest.